Sedimentology, Facies Associations and Sequence Stratigraphy of Falher divisions C and D of the Lower Cretaceous Spirit River Formation, West-Central Alberta, Canada - Casas, Jhonny E. (My University, 1996)
The Lower Cretaceous Falher Member (Spirit River Formation) in the Deep Basin of Alberta is composed of 5 coarsening-upward successions (A-E). Using an allostratigraphic approach, Falher D and C were each split into four shoreface units, deposited as a strandplain system trending east-west, with the open sea to the north.
The shoreface units of Falher D are characterized by very fine-to-fine-grained sandstones with swaley cross-stratification. Conglomerates and conglomeratic sandstones with cross-bedding are present in limited bodies trending east-west across the study area. The presence of swaley cross-stratification in the sandstones, combined with a Skolithos-Cruziana trace fauna assemblage, suggest that this facies represents wave- to storm-dominated deposition in a high-energy, upper to middle shoreface environment, above fair-weather wave base. Seaward, sandier-upward successions with hummocky cross-stratified very fine-grained sandstones interbedded with marine mudstones represent lower shoreface to offshore deposits.
The basal surface of Falher D overlies nonmarine deposits (Falher E) and is defined by a marine flooding surface (transgressive surface of erosion). Southward, all the facies become more continental and the marine flooding surface passes into a lagoon-on-nonmarine contact. Falher D contains a series of shingled marine sandstone lenses (units D1, D2, D3 and D4) separated by erosional surfaces interpreted as seaward-dipping ravinement surfaces. These indicate different phases of marine transgression and regression. In each unit the transgressive system tract can be preserved as barrier sands, transgressive lagoonal deposits, transgressive marine mudstones or coarse transgressive lag deposits. The highstand systems tract comprises a shoreface succession which prograded as a strandplain composed of sandy and conglomeratic shoreface deposits. In most of the units, upper shoreface conglomerates trend east-west parallel to the paleoshoreline. The top of Falher D is represented by aggradational coastal plain deposits.
The shoreface units of Falher C are characterized by very-fine to fine-grained sandstones with swaley cross-stratification. The presence of swaley cross-stratification in the sandstones, combined with a Skolithos-Cruziana ichnofossil assemblage, suggest that this facies represents wave- to storm-dominated deposition in a high-energy, upper to middle shoreface environment. Upper shoreface conglomerates and conglomeratic sandstones with crossbedding are present in limited bodies trending east-west.
The basal surface of Falher C across the study area is a composite of different marine flooding surfaces which overlie the aggradational coastal plain deposits of Falher D.
Falher C contains a series of shoreface units (C1, C2 and C3) separated by erosional surfaces. The transgressive systems tract in each unit can be preserved as transgressive marine mudstones and/or coarse transgressive lag deposits. The highstand systems tract comprises a succession of sandy and conglomeratic shoreface deposits, prograded as a strandplain system.
A major relative sea level fall ended the progradation of unit C3 producing a sequence boundary and a seaward shift of the shoreface facies beyond the northern edge of the study area. A relative sea level rise caused shoreface migration southward (landward) and the transgressive system tract is preserved as 4-7 m thick marine mudstones. Progradational shoreface deposits of unit C4 took place during highstand.
In Falher C, a north-south trending channel (CS) cuts into shoreface deposits of unit C4. This channel was probably feeding shoreface C4 during its progradation. The uppermost part of Falher C was filled by aggradational coastal plain deposits and the top of Falher C is defined by a marine flooding surface with erosional truncation during the shoreface retreat that defines the base of Falher B.
The duration of the transgressive-regressive event in each shoreface unit within Falher D and C has been estimated to be approximately 42,968 years, corresponding with fifth-order cyclic sea level changes. The changes in relative sea level during deposition of Falher D and C may be controlled by combined autocyclic and allocyclic processes.
Title: Sedimentology, Facies Associations and Sequence Stratigraphy of Falher Divisions C and D of the Lower Cretaceous Spirit River Formation, West-Central Alberta, Canada, Author: Jhonny E. Casas, Location: Thode